Administration of Oral Curcumin to Resistance Exercise after Immobilization Does Not Affect Skeletal Muscle Fiber Diameter in Rattus Norvegicus - I Putu Alit Pawana; Martha Kurnia Kusumawardani; Lydia Arfianti (Indonesian Journal of Physical Medicine & Rehabilitation, 2022)
ABSTRACTIntroduction: The aim of this study was to explore the effect of adding oral curcumin to resistance exerciseafter immobilization on the diameter of skeletal muscle fiber in Rattus Norvegicus.Methods: This was a post-test only study design on animal model. Subjects of the study were male Rattusnorvegicus strain Wistar, age 10-12 weeks old, weigh between 150-300 g, were immobilized at soleusmuscle for 2 weeks, then randomly allocated to 3 groups: (i) control group, (ii) resistance exercise, (iii)oral curcumin + resistance exercise. After 4 weeks of intervention, the diameter of the muscle fibers wasmeasured.Result: The results of this study showed a significant difference on the diameter of skeletal muscle fiberbetween control group and resistance exercise, as well as control group and resistance exercise + oralcurcumin (p<0.05). There was no significant difference between resistance exercise only and resistanceexercise + oral curcumin (p>0.05).Conclusion: Administration of oral curcumin to resistance exercise after immobilization does not affectskeletal muscle fiber diameter in Rattus Norvegicus.Keywords : curcumin, good health and well-being, immobilization, resist ance exercise, skeletal muscle.